Treatment of multiple sclerosis with rituximab: A Spanish multicenter experience - Gascón-Giménez, Francisco; Alcalá, Carmen; Ramió-Torrentà, Lluís; Montero, Paloma; Matías-Guiu, Jorge; Gómez-Estevez, Irene; Oreja-Guevara, Celia; Gil-Perotín, Sara; Blanco, Yolanda; Carcelén, María; Quintanilla-Bordás, Carlos; Costa, Lucienne; et al. (Frontiers in Neurology, 2023)
Introduction: Rituximab (RTX) is considered a potential therapeutic option for relapsing-remitting (RRMS) and progressive forms (PMS) of multiple sclerosis (MS). The main objective of this work was to investigate the effectiveness and safety of rituximab in MS. Patients and methods: Observational multicenter study of clinical and radiological effectiveness and safety of rituximab in RRMS and PMS. Results: A total of 479 rituximab-treated patients were included in twelve Spanish centers, 188 RRMS (39.3%) and 291 (60.7%) PMS. Despite standard treatment, the annualized relapse rate (ARR) the year before RTX was 0.63 (SD: 0.8) and 156 patients (41%) had at least one gadolinium-enhanced lesion (GEL) on baseline MRI. Mean EDSS had increased from 4.3 (SD: 1.9) to 4.8 (SD: 1.7) and almost half of the patients (41%) had worsened at least one point. After a median follow-up of 14.2 months (IQR: 6.5-27.2), ARR decreased by 85.7% (p < 0.001) and GEL by 82.9%, from 0.41 to 0.07 (p < 0.001). A significant decrease in EDSS to 4.7 (p = 0.046) was observed after one year of treatment and this variable remained stable during the second year of therapy. There was no evidence of disease activity in 68% of patients. Infusion-related symptoms were the most frequent side effect (19.6%) and most were mild. Relevant infections were reported only in 18 patients (including one case of probable progressive multifocal leukoencephalopathy). Conclusion: Rituximab could be an effective and safe treatment in RRMS, including aggressive forms of the disease. Some selected PMS patients could also benefit from this treatment.